Blast injury of the ear by massive explosion: a review of 41 cases. Issue 5 (16th February 2017) - Ballivet de Régloix, Stanislas; Crambert, A; Maurin, O; Lisan, Q; Marty, S; Pons, Y
Abstract : Background: Blast injuries in modern warfare are common, and the ear is often affected as it is an effective pressure transducer. This study aimed to evaluate military blast injuries of the ear. Methods: From May 2002 to October 2014, all patients referred to two military hospitals near Paris, France following exposure to massive explosions were analysed. Results: Among the 41 patients (82 ears), 36 of them reported tinnitus, 25 hearing loss, 14 earache and 8 vertigo. It was noted that 44% of the patients had tympanic membrane perforations and that this was bilateral in two-thirds of the cases. The hearing loss in 29% of the cases was pure sensorineural, in 55% it was mixed and in 15% it was a pure conductive hearing loss. There was no correlation between the impact of middle ear lesions and the severity of the inner ear injury. Three patients had a pharyngolaryngeal blast injury detected on the battlefield associated with blast lung injury, but only two of them had tympanic perforations. Nine tympanoplasty procedures were performed, of which 44% succeeded in sealing the perforation. Conclusions: Blast injuries of the ear are characterised by significant functional signs and are not correlated to otoscopic examinations. Sensorineural hearing loss is almost immediately final. When deciding on initial management, the status of the tympanic membrane does not provide any information about the risk of a primary blast injury of the lung; laryngeal nasofibroscopy seems a more relevant screening test.